Dollarization of the Banking System : Good or Bad? - De Nicolo, Gianni; Honohan, Patrick; Ize, Alain (World Bank, Washington, DC, 2014)
De Nicol Honohan, and Ize assess the benefits and risks associated with dollarization of the banking system. The authors provide novel empirical evidence on the determinants of dollarization, its role in promoting financial development, and on whether dollarization is associated with financial instability. They find that: The credibility of macroeconomic policy and the quality of institutions are both key determinants of cross-country variations in dollarization. Dollarization is likely to promote financial deepening only in a high inflation environment. Financial instability is likely higher in dollarized economies. The authors discuss the implications of these findings for financial sector and monetary policies.